2018
DOI: 10.1016/j.ijheatmasstransfer.2018.06.112
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of interaction between a freely moving solid particle and a freely moving liquid droplet by lattice Boltzmann method

Abstract: Solid particles and liquid droplets widely coexist in many industrial processes. Particle-droplet interactions critically influence the dynamics of those processes. In this study, the interactions between a freely moving solid particle and a freely moving liquid droplet are numerically investigated using the lattice Boltzmann method. Until now the open literature on such topic is quite sparse. Through the present numerical investigation, two regimes to classify the interactions between a freely moving solid pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…4(a) at a non-dimensional time, 3.75. It can be observed that the droplet interaction with the solid particle captured in the present model is similar to the behavior of the droplet that Yang and Chen 38 predicted. In addition, the time-dependent velocity of moving solid particles is also compared for two wetting parameters, hydrophobicity and hydrophilicity, and is shown in Fig.…”
Section: Numerical Modelingsupporting
confidence: 81%
See 2 more Smart Citations
“…4(a) at a non-dimensional time, 3.75. It can be observed that the droplet interaction with the solid particle captured in the present model is similar to the behavior of the droplet that Yang and Chen 38 predicted. In addition, the time-dependent velocity of moving solid particles is also compared for two wetting parameters, hydrophobicity and hydrophilicity, and is shown in Fig.…”
Section: Numerical Modelingsupporting
confidence: 81%
“…It can also be noticed that the behavior of solid particle movement is captured well by the present model for both the wetting parameters with the data that are taken from the study of Yang and Chen. 38 These well-predicted qualitative and quantitative data show the ability of the present model for analyzing the behavior of respiratory droplets in an open environment with pollutants.…”
Section: Numerical Modelingsupporting
confidence: 55%
See 1 more Smart Citation
“…However, in reality, droplet and particle can freely move before and after the collision. In a recent study, Yang et al, [22] used 2D numerical simulations to investigate the drop-particle collision when both droplet and particle are freely moving. They noted that when a hydrophobic particle is tested, the droplet and particle would be separated after impact.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies were focused on relative velocity between particle and droplet. Recently, Yang et al [9] simulated the interaction between freely moving particle and droplet, and analyzed the results according to size and eccentricity ratio. It was carried out in plane 2D geometry which can be quite different from real physics.…”
Section: Introductionmentioning
confidence: 99%